Reinterpreting higher education quality in response to policies of mass education: the Australian experience - Pitman, Tim (Routledge Taylor & Francis Group, 2014)
This article explores the relationship between mass education, higher education quality and policy development in Australia in the period 2008–2014, during which access to higher education was significantly increased. Over this time, which included a change of national government, the discursive relationship between mass higher education and higher education quality shifted from conceptualising quality as a function of economic productivity, through educational transformation and academic standards, to market competition and efficiency. Throughout, the student was more often positioned as a servant towards higher education quality, rather than its benefactor.